Study on the Application of O2O Peer Tutor Collaborative Health Management Program in Rural Diabetes Patients with Non-standard Treatment - JIA Honghong, DU Qiuhui, ZHANG Zichen, ZHOU Yuqiu (Zhongguo quanke yixue)
Background The phenomenon of non-standard treatment of diabetes patients in rural areas is particularly serious. Diabetes health management is focused on preventing and controlling diabetic complications in rural areas of China, as well as lowering disability and death rates. Objective To explore the effects of O2O peer mentor collaborative health management on the risk perception and diabetes management self-efficacy in rural patients with non-standard diabetes treatment. Methods A total of 90 diabetic patients with non-standard treatment in Lamadian Town, Ranghulu District, Daqing City from April to November 2023 were selected as the study subjects by convenience sampling method, and randomly assigned 45 patients to the experimental group and 45 to the control group. The experimental group adopted O2O peer mentor collaborative health management scheme, the intervention lasted for 6 months, and the control group adopted conventional chronic disease health management. A comparison was made between the two groups' risk perception and self-efficacy in managing their diabetes. Results The study was concluded with 42 cases in the experimental group and 41 instances in the control group. Following the intervention, the experimental group and control group had scores on the diabetes risk perception scale of (43.86±7.00) and (32.56±4.24), there was a statistically significant difference between them (t=8.864, P<0.001). Similarly, the experimental group and control group had scores on the diabetes management self-efficacy scale of (100.45±16.74) and (75.54±13.82), there was a statistically significant difference between them (t=7.384, P<0.001) . Conclusion The O2O peer mentor collaborative health management program can effectively improve the risk perception and diabetes management self-efficacy of rural patients with non-standard diabetes treatment, and improve their health management level.